EPISTEMOLOGIC GROUNDS FOR RESEARCH IN EDUCATION: APPROACHES TO HISTORICAL DIALECTICAL MATERIALISM - Pelegrini, Anderson de Oliveira; Tuim Viotto Filho, Irineu Aliprando [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
Aims to present the theoretical-philosophical and epistemological aspects justifying a study that monitored and examined an intervention project conducted among the students of a Municipal Elementary School at Presidente Prudente/SP/Brazil, in order to understand the historical and social movement building social relationships within the school and its development in the awareness process of the students. The results of this work could show us the possibilities of understanding the building process of the social relationships and the students consciouness inside the school as dialectical historical materialism method and historical-cultural theory defends for the human being process of development.
Keywords: Search intervention at school; Dialectical historical materialism; Education and awareness building